JENIS BURUNG PEMANGSA DI RESORT TEGALLEGA TAMAN NASIONAL GUNUNG GEDE PANGRANGO - Agus Pambudi Dharma; M. Meitiyani; Winda Sulpia; Wilda Rosalina; Ahmad Rizky Mudzakir (LP4MK STKIP PGRI Lubuklinggau, 2022)
The presence of birds of prey at the ecosystems in Gunung Gede Pangrango National Park (TNGGP) is very important as the top predator that helps stabilizing the pyramid or food chain. This study purpose to examine the diversity of raptors at Tegallega Resort in TNGGP. Fieldwork had been conducted from June 2021 to Maret 2022 and Oktober 2022 at this resort. Data collection used 1 km line transect where the point counts applied. Three line transects with 1 km in between distance were visited 11 times during the field data collection. The result shows that Tegallega Resort has five raptor species: crested serpent-eagle Spilornis cheela, changeable hawk-eagle Nisaetus limnaeetus, javan hawk-eagle N. bartelsi, Eurasian sparrowhawk Accipiter nisus, and barn owl Tyto alba. The eagles and hawk are protected by Indonesian regulations, while the owl is least concern species according to IUCN Redlist. When found the eagles flies in circles (soaring) with a sound when the weather is sunny and hot.